2021
DOI: 10.1016/j.puhe.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of the general population about Coronavirus disease 2019 (COVID-19): a systematic review and meta-analysis with policy recommendations

Abstract: Objectives This study aimed to investigate and synthesize the current evidence on knowledge, attitudes, and practices (KAPs) of the general population regarding COVID-19. Study Design Systematic review and meta-analysis. Methods We conducted a systematic search on PubMed/LitCovid, Scopus, and Web of Sciences databases for papers in the English language only, up to 1 January 2021. We used the Joanna Briggs Institute (JBI) checklist developed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 87 publications
5
55
1
7
Order By: Relevance
“…This level of food safety knowledge amongst university students has been previously reported ( 14 , 16 , 22 , 23 , 30 ). A meta-analysis reported overall KAP scores regarding COVID-19 to be 78.9, 79.8, and 74.1, respectively ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This level of food safety knowledge amongst university students has been previously reported ( 14 , 16 , 22 , 23 , 30 ). A meta-analysis reported overall KAP scores regarding COVID-19 to be 78.9, 79.8, and 74.1, respectively ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis report revealed that COVID-19-related knowledge was found high in the general population, but practice of preventive measures needs to be promoted. 25 Risk perception to COVID-19 was one of the main determinant factor for the adoption and utilization of COVID-19 prevention measures. 51 Peoples’ perceived severity has a stronger effect than perceived susceptibility in the engagement of protective behaviors against the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Generally, a systematic review and meta-analysis report revealed that more than two-thirds of study participants in the general population had good knowledge and favorable attitude toward the pandemic. 25 In Ethiopia, the majority of the urban population have good knowledge about COVID-19. 26 , 27 However, adhering to COVID-19 prevention methods was not satisfactory despite the increment of cases and death in the country.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that during the period of resuming work and increasing production, the effect of prevention and control of pneumonia is greatly affected by the knowledge, attitudes and practices (KAP) of the people returning to work. The level of knowledge of a disease can affect people's attitudes and practices, on the other hand, negative attitudes and practices can increase the risk of death from disease (16,17). Therefore, the purpose of this study is to assess the KAP status quo and explore the possible influencing factors of different occupational groups, so as to provide valuable information for countries and regions that have returned to work or are ready to return to work.…”
Section: Introductionmentioning
confidence: 99%